The drifting subpulse and nulling of PSR B0820 + 02 observed with FAST. Issue 1 (6th February 2023) - Zhi, Qijun; Xu, Xin; Shang, Lunhua; Bai, Juntao; Dang, Shijun; Lu, Jiguang; Dai, Shi; Zhao, Rushuang; Wen, Zhigang; Qiao, Guojun; Dong, Aijun
ABSTRACT: PSR B0820 + 02 is known to exhibit the subpulse drifting phenomenon, which carries vital information about the pulsar radiation process. In this work, we studied the subpulse drifting of PSR B0820 + 02 at a central frequency of 1250 MHz using the Five-hundred-meter Aperture Spherical radio Telescope (FAST). Thanks to the superior sensitivity of FAST, we found that PSR B0820 + 02 shows four distinct subpulse drifting modes (A, B, C, and D), the last three of which have not been reported before. The drifting periodicities of these four modes are found to be 4.3 P 1, 6.4 P 1, 8.2 P 1, and 10.3 P 1 ( P 1 is the pulse period), respectively. No null pulse is found in our FAST observation. By comparing the energy distribution of single pulses of all four modes, we found that mode A has the highest energy and mode D has the lowest energy. Finally, we interpreted the drift modes in terms of the carousel model, and showed that if B0820 + 02's different drift modes are due to aliasing effects, the carousel rotation period of P 4 lies in the range 29 P 1 –33 P 1 . The new subpulse drifting phenomena of PSR B0820 + 02 reported here provide a unique opportunity for understanding the mechanism and radiation geometry of pulsar radio radiation.